Dynamic landscape of multi-elements in PM2.5 revealed by real-time analysis. (December 2022) - Ji, Xiaomeng; Qin, Ruiliang; Shi, Chunzhen; Yang, Lin; Yao, Linlin; Deng, Shenxi; Qu, Guangbo; Yin, Yongguang; Hu, Ligang; Shi, Jianbo; Jiang, Guibin
Graphical abstract: Highlights: PM2.5 were directly introduced for real-time monitoring the contents of 12 elements. Highly time-solution and sensitivity were fulfilled by novel online analysis. Toxic elements like Pb, As and Cd have an upward trend at dusk. Exposure risk discrepancy was revealed by dynamic changes of 12 elements in PM2.5. Abstract: Metal components in fine particulate matter (PM2.5 ) are closely associated with many adverse health outcomes. Dynamic changes of metals in PM2.5 are critical for risk assessment due to their temporal variations. Herein, an online method for real-time determination of multi-elements (As, Cd, Cs, Cu, Fe, Mg, Mn, Pb, Rb, Sn, Tl, and V) in PM2.5 was established by directly introducing air samples into inductively coupled plasma mass spectrometry (ICPMS). Meanwhile, a quantified method using metal standard aerosols (Cr, Mo, and W) and high time resolution for 3.3 min online measurement was developed and validated. The limits of detection were in the range of 0.001–6.30 ng/m 3 for different metals. Subsequently, the real-time contents of multi-elements in PM2.5 for 12 h over 33 days were measured at different air qualities. Temporal variations of crustal elements like Fe, Mg are similar to PM2.5, whereas toxic elements (Pb, As and Cd) have upward trends at dusk. This denoted the association with various emission sources and different exposure concentrations of metals. In addition to the acquisition of real-time information, online analysis of multi-elements in PM2.5 is beneficial for atmospheric monitoring and provides critical insights into the different exposure risks of metals in PM2.5 at varying times.